Experimental study of infrared – assisted heat pump drying of lime slices - Nguyen , Minh Ha; Ha , Anh Tung (Journal of Technical Education Science, 2021)
This paper describes the experimental drying of lime slices using an infrared –assisted heat pump dryer. Experiments were carried out on a heat pump dryer model with a capacity of 1 HP integrated with 2000 W infrared radiator whose power can be varied from 0% to 100%. Experiments have been performed with the drying capacity of 1,2 kg/batch and the drying air velocity of 1,2 m/s. Three evaluations were considered: the effect of material thickness on drying time; the effect of temperature in drying chamber and intensity of infrared radiation on drying time, power consumption and product quality. The results showed that the drying process having 3 mm thickness of lime slices, the temperature in the drying chamber of 42,5¸45oC and the radiation intensity of 110¸300W/m2 was the good effective drying range. In addition, the study formulated a linear regression equation for the drying time relationship with drying chamber temperature and infrared radiation intensity. This mathematical model can be used as reference to determine actual drying time as well as a helpful tool for designing infrared - heat pump dryer.